Proteomic Analysis of Serum Lysine Acetylation in Uyghur Patients With T2DM - Wang, Xuemei; Cai, Weijuan; Yin, Liang (Frontiers in Molecular Biosciences, 2022)
Lysine acetylation is a reversible modification process after protein translation, which plays a key regulatory role in various metabolic diseases such as diabetes. The prevalence of type 2 diabetes mellitus (T2DM) in the Uyghur population is high, but the acetylation status of proteomics in Uyghur with T2DM is still unclear. Herein, we performed a quantitative proteomic study of lysine acetylation in T2DM patients using Tandem Mass Tags (TMTs) labeling, acetylation enrichment techniques, and high-resolution liquid chromatography-tandem mass spectrometry. We quantified 422 acetylation sites on 120 proteins, of which 347 sites of 103 proteins contained quantitative information. Compared with the control, we found that a total of eight acetylated sites within proteins were significantly differentially expressed with three upregulated and five downregulated, including histones H4 and H3.3C. Meanwhile, we completed bioinformatics analysis, including protein annotation, functional classification, functional enrichment, and cluster analysis, based on functional enrichment. In addition, the mRNA (ApoB-100, histones H4 and H3.3C) and protein (histones H4 and H3.3C) levels were verified through 60 samples. Besides, we also performed histone H4 chromatin immunoprecipitation analysis at the level of INS-1 cells. These could be potentially useful markers for the prediction of prediabetes and also provided a basis for the pathogenesis of T2DM.